1999
DOI: 10.1097/00007890-199911270-00022
|View full text |Cite
|
Sign up to set email alerts
|

Strain Specific Effects of Cytomegalovirus on Endothelial Cells: Implications for Investigating the Relationship Between CMV and Cardiac Allograft Vasculopathy1

Abstract: These data demonstrate that the genetic heterogeneity of CMV is associated with differences in transplant-relevant biologic activity even among clinical isolates. The relationship between CMV and chronic rejection may be difficult to determine given the heterogeneous nature of this complex virus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2002
2002
2008
2008

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…HCMV decreases the expression of MHC class I molecules on fibroblasts 12 and on endothelial cells 25 and partially downregulates surface expression of MHC class I molecules on human macrophages 26 by multiple mechanisms. The finding of down-regulation of MHC class I molecules on DCs is in agreement with these studies.…”
Section: Discussionmentioning
confidence: 99%
“…HCMV decreases the expression of MHC class I molecules on fibroblasts 12 and on endothelial cells 25 and partially downregulates surface expression of MHC class I molecules on human macrophages 26 by multiple mechanisms. The finding of down-regulation of MHC class I molecules on DCs is in agreement with these studies.…”
Section: Discussionmentioning
confidence: 99%
“…Another mechanism of cellular accumulation occurs through SMC proliferation at the site of vascular injury. CMV infection of endothelial cells induces the release of growth factors and cytokines, including fibroblast growth factor and platelet-derived growth factor BB, which are potent stimuli of SMC proliferation (30). Furthermore, HCMV infection up-regulates expression of the CC chemokine RANTES in SMCs and fibroblasts (23,32).…”
Section: Discussionmentioning
confidence: 99%
“…[25][26][27][28] Toyoda et al 29 reported that elevated AECA levels were seen in 80% of transplant recipients with evidence of CMV infection, suggesting that CMV infection may trigger AECA synthesis. In the present study, nine recipients had CMV infections, and in these patients, the serum levels of AECA against HUVEC and MvE were enhanced a few weeks after CMV infection.…”
Section: Discussionmentioning
confidence: 99%